STRATEGIC POSTPONEMENT IN FAST FOOD OPERATIONS: ENHANCING ORDER FULFILMENT IN A FRONTIER EMERGING MARKET - Paul MUKUCHA; Divaries Cosmas JARAVAZA; Fanny SARUCHERA (Business Excellence and Management)
This research explores the effect of strategic postponement on order fulfilment performance within Zimbabwe's fast-food sector, a vital yet underexamined area in Sub-Saharan African market studies. This investigation is propelled by the notable lack of empirical scrutiny on postponement strategies in the region's fast-food industry, particularly within the challenging context of Zimbabwe's volatile economy. Such conditions offer limited managerial insights into the correlation between form postponement and order fulfilment efficiency, diverging from the trends observed in more developed and saturated markets. Utilising a causal research framework, the study gathered data from a survey of 100 fast food establishments in Harare, employing Multivariate Analysis of Variance (MANOVA) for data analysis, complemented by Bonferroni correction to mitigate type 1 error from multiple comparisons. Findings indicate that restaurants implementing a postponement strategy significantly outperform their counterparts in order fulfilment metrics. The study advocates for the adoption of postponement strategies by fast food operators to enhance order fill rates, accuracy, and cycle times, thereby navigating the complexities of emerging markets more effectively. Despite its insightful contributions, the study acknowledges its geographical limitation to Zimbabwe, attributed to budgetary restraints.